Structure and thermodynamic properties of zircon-coffinite solid solutions according to the semiempirical atomistic simulation data - Zamyatin, D. A.; Shchapova, Yu. V.; Votyakov, S. L.; Eremin, N. N.; Urusov, V. S. (Glass physics and chemistry, 2013)
Structure and thermodynamic properties of zircon, coffinite, and zircon-coffinite solid solutions were subject to semiempirical atomistic simulation on the assumption of compositional disordering of mixed crystals: (Zr 1 − x , U x )SiO 4 , where x = 0.02, 0.05, 0.08, 0.11, 0.14, 0.28, 0.50, 0.72, and 0.86. The solid solutions significantly depart from the Vegard and Retgers laws. The (Zr 1 − x , U x )SiO 4 mixed crystal structure is characterized by anisotropic expansion (largely in the a and b directions) under growth in x related to anisotropy of structural relaxation degree of the cation-oxygen interatomic spacing in the (Zr, U)O 8 polyhedron. Increase in x parameters is accompanied by increase in average size of cation-oxygen polyhedrons and silica-oxygen tetrahedrons and by growth of interatomic spacing dispersion; maximum dispersion values are observed at x = 0.5–0.6. The distortions in local structures of ZrO 8 and UO 8 dodecahedrons and silica-oxygen tetrahedrons in the solid solution were analyzed on the basis of calculated functions of interatomic distance distribution. The obtained results demonstrate the possibility to assess numerically the structural (geometrical) disordering degree of the compositionally disordered solid solution depending on its composition. The calculated thermodynamic characteristics of solid solutions forecast the following solubility range limits: 2 mol % USiO 4 in zircon and 5 mol % ZrSiO 4 in coffinite under ∼1750 K.